Development of RuO2/CeO2 heterostructure as an efficient OER electrocatalyst for alkaline water splitting. (24th July 2020) - Galani, Sunil M.; Mondal, Aniruddha; Srivastava, Divesh N.; Panda, Asit Baran
Abstract: Here, the synthesis of RuO2 loaded CeO2 with varying amount of Ru loading with enhanced amount of Ce 3+ and surface area, through synthesis of CeO2 using cerium ammonium carbonate complex as procure followed by Ru loading by impregnation and calcination at 300 °C, is presented. Corresponding characterizations by XRD, SEM, TEM, XPS of all the samples reveal the formation of highly crystalline mesoporous CeO2 nanoparticles with uniformly dispersed RuO2 particles on the CeO2 surface having approximately 45% Ce 3+ . All the samples were utilized as oxygen evolution reaction (OER) catalyst for electrocatalytic H2 generation through water electrolysis. Electrocatalytic experiments reveal that synthesized 1 wt% RuO2 loaded CeO2 (1-RuO2 /CeO2 ) showed superior OER activity. A quite low over-potential of 350 mV is required to attain a current density of 10 mA/cm 2 ( ɳ 10 ), with a Tafel slope of 74 mVdec −1 for OER in 1 M KOH solution. The synthesized 1-RuO2 /CeO2 electrocatalyst also exhibited superior long term stability in basic medium and redox atmosphere. Highlights: Simple aqueous solution based Chemical Synthesis of RuO2 –CeO2 hetero nanostructures. Synthesis is based on formation of CeO2 spheres followed by Ru impregnation. 1 wt% RuO2 –CeO2 showed excellent electrocatalytic OER activity in 1 M KOH solution. Showed low overpotential of 350 mV for 10 mA/cm 2 & Tafel slope of 74 mVdec −1 for OER. Exhibited superior electrochemical stability in basic as well as redox environment.